2019
DOI: 10.1111/jwas.12617
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and growth conditions of Vibrio parahaemolyticus strains with different virulence degrees that cause acute hepatopancreatic necrosis disease in Litopenaeus vannamei

Abstract: The phenotypic characteristics and growth kinetics at several temperatures, salinities, and pH values of three Vibrio parahaemolyticus (Vp) strains with different virulence and one nonpathogenic strain were evaluated. Independent of the virulence of the strain, a high metabolic diversity was found, which yielded different colored phenotypes on the CHROMagar™ Vibrio. All strains were resistant to ampicillin and carbenicillin, and Vp AHPND+ organisms were the most sensitive to enrofloxacin. The exponential growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Soto‐Rodriguez et al . (2019) compared the growth kinetics of three Vp AHPND strains with distinct virulence and one nonpathogenic strain at different pH and NaCl concentration. However, no relation between the bacterial growth and degree of virulence was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Soto‐Rodriguez et al . (2019) compared the growth kinetics of three Vp AHPND strains with distinct virulence and one nonpathogenic strain at different pH and NaCl concentration. However, no relation between the bacterial growth and degree of virulence was observed.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, mortality was higher at lower saline concentration, finding a positive correlation with the expression of pirA Vp gene. Although more experiments are needed to determine the influence of salinity on the expression of pirAB Vp , these experiments corroborate that the toxin can be expressed at different salinities [82] and that the management of saline concentration in shrimp culture can be an important factor to control Vp infectivity.…”
Section: Environmental Factorsmentioning
confidence: 58%
“…The difference in the final survival lay in the fact that V. parahaemolyticus is a halophilic bacterium which reproduces more efficiently in environments with high salinities. Soto‐Rodriguez et al., (2019) found that Vp AHPND bacteria are able to reproduce in salinities between 5 ppt and 100 ppt, while Lekshmy et al., (2014) determined that there is a positive correlation between salinity and bacterial density in Vibrio parahaemolyticus isolates. It is possible that the increased bacterial density led to the production of a greater amount of pirAB toxin at the higher salinities.…”
Section: Discussionmentioning
confidence: 99%